MANAGEMENT PROBLEMS IN THE FARMING OSTRICH - Miljković, Biljana; Prodanov, Mirko; Pavlovski, Zlatica; Radanović, Oliver; Pavlović, Ivan; Tolimir, Nataša (University Ss. Cyril and Methodius in Skopje, 2011)
Recent interest in ostrich farming increased the demand for information about this species and how to manage it in a commercial environment. This bird is unique, being the largest living bird, measuring up to 2.75 m in height and up to 150 kg in mass. The bird is unable to fly, but the structure of the wing bones, the presence of air sacs, some pneumatic bones and presence of the pygostyle, strongly suggest that the ostrich evolved from a flying ancestor. The ostrich spends its time walking around its environment, only running if threatened. These birds can reach the speed of approxi-mately 60–70 km/h. The leg anatomy reflects the walking lifestyle of the ostrich and it has only two toes. Our collection of information started with some particular aspects of ostrich chick biology (chick quality, residual vesica felea, growth rates, mortality, leg problems, post-hatch) having significant impact on the rearing systems employed. This aspect of husbandry is a critical phase of commercial production, was in the past and remains today the cause of significant problems in the majority of countries where ostrich farming is a novel enterprise. There is a wide variety of different rearing conditions, all of which are successful to different extent. As it is common with commercial poultry production, the best results are achieved with the highest quality day-old chicks. In this work the authors try to connect collected information and their personal field experience in rearing 3 months old ostrich chicks from France during quarantine time as well as later, during application of some prophylactic and therapeutic measures including patho-anathomy and laboratory examination.
Keywords: ostrich; characteristic and farming